2011
DOI: 10.3109/01443615.2011.553693
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovary syndrome and the peripheral blood white cell count

Abstract: This retrospective cross-sectional study examined if the white cell count (WCC) is increased in women with polycystic ovary syndrome (PCOS) and if so, is it due to PCOS or to the associated obesity? Body mass index (BMI) was calculated and body composition was measured using bioelectrical impedance analysis. Of the 113 women studied, 36 had PCOS and 77 did not. The mean WCC was higher in the PCOS group compared with the non-PCOS group (8.9 × 10(9)/l vs 7.4 × 10(9)/l p = 0.002). This increase was due to a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 24 publications
6
27
0
Order By: Relevance
“…Therefore, we consider that this condition should be further discussed, and more comprehensive studies to enlighten the correlation between MPV, obesity, and PCOS are needed. Increased leucocyte count is an independent risk and prognostic factor in the development of inflammation and atherosclerosis [17], and there are several studies reporting increased leucocyte counts in patients with PCOS [4,7,15,16,35]. In our study, leucocyte counts were similar in patients with PCOS and controls; still, differential count of leucocytes revealed that patients with PCOS had higher neutrophil count and ratio, basophil count and lower lymphocyte count, compared to controls.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Therefore, we consider that this condition should be further discussed, and more comprehensive studies to enlighten the correlation between MPV, obesity, and PCOS are needed. Increased leucocyte count is an independent risk and prognostic factor in the development of inflammation and atherosclerosis [17], and there are several studies reporting increased leucocyte counts in patients with PCOS [4,7,15,16,35]. In our study, leucocyte counts were similar in patients with PCOS and controls; still, differential count of leucocytes revealed that patients with PCOS had higher neutrophil count and ratio, basophil count and lower lymphocyte count, compared to controls.…”
Section: Discussionsupporting
confidence: 47%
“…Additionally, increased leucocyte counts were found to be an additional independent marker and prognostic factor in the development of inflammation and atherosclerosis [4,7,[15][16][17]. In recent years, neutrophil to lymphocyte ratio (NLR) has gained a popularity in the detection of inflammation in different inflammatory diseases such as PCOS, DM, ulcerative colitis, and hypertension, and it has been shown that NLR is correlated with hsCRP levels [4,18,19].…”
Section: Introductionmentioning
confidence: 97%
“…The main novel finding of this study, however, is the leucocytosis and lymphocytosis in PCOS compared to normal controls even after eliminating the influence of obesity. Herlihy et al [7] and Phelan et al [15] found similar results in European women. This implies there is an independent correlation between leucocytosis and PCOS beyond BMI, although it is not clear what underlies this effect.…”
Section: Commentssupporting
confidence: 56%
“…In addition, 38-88% of PCOS women appear overweight or obese [3], which is thought to be a pro-inflammatory state [4]. Recent studies have observed that PCOS women are often confronted with lowgrade chronic inflammation [5] and have higher peripheral white blood cell (WBC) counts [6,7]. Differential WBCs, e.g.…”
Section: Introductionmentioning
confidence: 98%
“…For example, some studies have shown that IL-18 cytokine is closely associated with insulin resistance and metabolic syndrome, including high blood pressure, hyperlipidemia, diabetes mellitus, obesity, and hypertension (30,31). Moreover, other studies have also shown that an increase in leukocytes in women with PCOS is closely associated with insulin resistance through homeostasis model (32-34). …”
Section: Discussionmentioning
confidence: 94%